A Design of Electrical Permanent Magnet Generator for Rural Area Wind Power Plant - Muhammad Irfan; Ermanu Azizul Hakim; Diding Suhardi; Nur Kasan; Machmud Effendy; Ilham Pakaya; Amrul Faruq (Institute of Advanced Engineering and Science, 2018)
This paper aims to design and simulate an Electrical Permanent Magnet Generator (EPMG) for rural area wind power plant. The generators available in the market mostly are a kind of high speed induction generator which requires high rotational speed and an electricity to generate a magnetic field. In this project, a radial flux generator is designed to have a low speed rotation using permanent magnet type Neodymium Iron Boron (NdFeB). Software used for designing is Finite Element Method (FEM) Magnet software basis. The model also examined with Simulink/Matlab environment. Extensive modifications are applied to get optimum result by changing generator diameter, number of coils, the copper wire diameter, number of poles, and used slots. The simulation results obtained generator speed 500rpm, the average series voltage is 145 Vrms, the generator requires 18cm diameter, number of turn for each coil is 55, diameter of the copper wire used is 0.6mm, and number of poles is 8 pairs and 12 unit slots.